(untitled) (Bangladesh Journal of Zoology, 2018)
Investigations on Snapper fish of the genus Lutjanus were conducted from October 2015 to April 2016 in the coral ecosystem of St. Martin’s Island, Bangladesh. Twenty one individuals of 8 species of Lutjanus were collected from local fishermen. Both morphological characters and DNA barcoding approach by mitochondrial cytochrome oxidase I subunit (COI) were used to confirm the identification of all species. Present study recorded the first national occurrence of two reef associated Lutjanus species (L. xanthopinnis and L. indicus). In addition six species (L. rivulatus, L. lutjanus, L. vitta, L. lemniscatus, L. fulviflamma and L. johnii) were re-described. Distinct morphological differentiation were found between more closely related species L. xanthopinnis, L. vitta and L. lutjanus. Three different appearances of L. johnii, two different appearances of L. rivulatus and L. lemniscatus were confirmed as same species. Phylogenetic analysis showed monophylotic clade for conspecific individuals and paraphyletic clade for congeneric individuals. Average genetic divergence for intraspecific level was 1.5% and 12.5% for interspecific level. Current study increased the number of Lutjanus species in Bangladesh from 15 to 17 and extended the distribution range of those new recorded species in northeastern part of the Bay of Bengal. Bangladesh J. Zool. 46(2): 239-253, 2018